CONFIDENCE IN COMMUNICATION CHANNEL AS A FACTOR OF INFLUENCE ON CONSUMER BEHAVIOR - A. Timokhovich (Вестник университета)
This article is devoted to the analysis of results of the empirical research of studying the confidence phenomenon in channels of distribution of advertising information. The article provides the connection between confidence in channel of distribution of advertising information and confidence in advertising messages transmitted on a certain channel. The article provides a rationale for the connection influence on consumer behavior.